Adsorption of tetracycline onto alumina: experimental research and molecular dynamics simulation. Issue 11 (2nd March 2016) - Zhao, Bin; Ji, Yingxue; Wang, Fenghe; Lei, Hua; Gu, Zhongzhu
Abstract: Adsorption characteristics of tetracycline (TC) onto alumina were investigated according to batch adsorption experiments, and the mechanism was dissected at molecular level by molecular dynamics (MD) simulation. Results indicated that the adsorption was influenced by alumina dosage, temperature, and oscillating frequency. The optimal temperature was 25°C. By increasing the alumina dosage from 0.1 to 2.0 g/L, the removal efficiency of TC increased from 53.73 to 86.44%. With the increase in oscillation frequency from 90 to 200 r/min, the removal efficiency of TC increased by 28.78%, indicating that the increase of frequency could enhance the adsorption of TC. The adsorption behavior fitted well with the pseudo-second-order model ( R 2  > 0.99). MD simulations revealed that TC molecule structure was deformed when it clung to the alumina crystal. The magnitude of deformation energy (99.893 kcal/mol) was far less than that of non-bond energy (319, 643.811 kcal/mol). Analysis of radial distribution function showed that TC could be adsorbed effectively by alumina mainly through non-bond interaction.